Necrotising fasciitis of the thigh secondary to a perforated rectal cancer - Highton, L.; Clover, J.; Critchley, P. (Journal of plastic, reconstructive & aesthetic surgery, 2009)
We report a rare case of rectal cancer presenting with necrotising fasciitis of the posterior thigh. Perforation of a rectal cancer adjacent to the piriformis muscle provided a route for bowel contents to travel into, and contaminate, the posterior compartment of the thigh. This case highlights the need for prompt diagnosis, urgent aggressive surgical debridement and consideration of a rare underlying cause in the management of necrotising fasciitis.